The Implementation of the Nahwu Match Game through the Cooperative TGT Model to Enhance Students’ Nahwu Proficiency at MTs Taswirul Afkar - M. Ulul Azmi; Saefullah Azhari; Nurul Istiqomah (Arfannur: Journal of Islamic Education, 2026)
One of the fundamental aspects of Arabic grammar is nahwu, which governs rules of sentence structure and syntax. Nevertheless, its complexity often poses challenges for students, especially in grasping basic concepts such as word inflection, sentence order, and syntactic functions. To address this issue, the researcher developed an educational game titled “Nahwu Match”, utilizing manual media (colored cards and a scoreboard) and integrated within the cooperative learning model of Teams Games Tournament (TGT). This innovation aimed to foster active learning by engaging students in group activities, where they identified and matched Arabic word functions while reinforcing their understanding of sentence structures through competitive tournaments. The study was conducted with eighth-grade students at MTs Taswirul Afkar, focusing on evaluating the effectiveness of the game in improving students’ nahwu competence, particularly in identifying and analyzing sentence components. Employing a quantitative approach, the research applied a quasi-experimental one-group pretest-posttest design involving 20 participants. Data were collected through objective tests, consisting of multiple-choice and essay questions administered before and after the treatment. The results were analyzed using descriptive statistics and a Paired Samples T-Test. Findings showed a substantial increase in the mean score, from 46.50 in the pretest to 80.50 in the posttest, with a significance value of 0.000 < 0.05. These results led to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁), indicating significant improvement in students’ achievement. In conclusion, the application of “Nahwu Match” through the TGT cooperative model proved effective in enhancing learning outcomes while simultaneously creating an engaging, competitive, and collaborative classroom atmosphere.